Analysis of Potential Cropping Seasons of Cayenne Pepper (Capsicum frustescens L.) Based on Water Balance in Alfisol Dryland, Tuban Regency, East Java, Indonesia - Zuhdi, AH. Maftuh Hafidh; Indarwati, Lisa Dwifani (Department of Agronomy and Horticulture, IPB University, 2024)
Dryland agriculture is crucial for understanding how to effectively manage land water for the crops. Water balance analysis plays a pivotal role in comprehending the hydrological cycle and water availability for crop production. The Tuban Regency is one of the fifth largest cayenne pepper-producing areas in East Java, Indonesia, particularly in Grabagan and Bancar Districts. However, for sustainable growth, it is imperative to extend cultivation to other sub-districts within Tuban Regency. In the cultivation of cayenne pepper, attention to soil water availability is important due to its susceptibility to drought, directly impacting vegetative growth and overall plant production. This research aims to establish a planting pattern for cayenne pepper based on water balance analysis in Alfisol drylands within Montong, Kerek, and Singgahan Districts of Tuban Regency. The study, conducted from July to September 2023, employed Thornthwaite and Mather water balance analysis,drought index assessment, and day without rain analysis. The research findings reveal variations inwater balance conditions within the study areas, with Montong and Kerek Districts experiencing a land water surplus for three months and a nine-month deficit. Singgahan District, on the other hand, encountered a surplus for four months and a deficit for eight months. The drought index indicates a high level, peaking in September for Montong (87%), Kerek (91%), and Singgahan (87%) Districts. Cayenne pepper plants exhibit the potential for annual cultivation in Alfisol drylands of Montong, Kerek, and Singgahan Districts, with a growing duration of six months. The optimal planting window spans from December to May, followed by potentially a second planting in June and July for crops with a minimum available water value exceeding 19% or those with a shorter harvest life. From August to November, the land lies fallow due to a soil water availability that is close to 0% and a 27% risk of days without rain in the extreme drought category, rendering the soil unsuitable for growing crops.